The influence of baby boomers' perceptions of well-being on their plan to age-in-place post-retirement. (October 2022) - Emerson, Eric J.; Ford, Robert C.; Simsek, Koray D.
Abstract: As baby boomers contemplate retirement, it is important to understand what, how, and where they plan to maximize their well-being. The senior living industry is especially interested as it considers how to apply hospitality strategies to increase its attractiveness to the boomer market about where they will spend their post-retirement years. Surprisingly, there is little research on what these prospective customers want in post-retirement living accommodations that maximizes their well-being. This study aims to fill this knowledge gap by assessing whether the elements of well-being influence baby boomers' pre-retirement plan to age-in-place after retirement. Since technology is increasingly being used to provide the elements of well-being, this cohort's affinity for technology was also measured to assess its influence as a moderator on the plan to age-in-place. Findings revealed a relationship between baby boomers' perception of their well-being needs and their decision to age-in-place while technology did not moderate these assessments. Highlights: The study investigated the influence of the elements of well-being on aging-in-place. The study assessed the influence of affinity for technology on that decision. The study sample focused on pre-retirement baby boomers. The study found some elements of well-being are more influential on aging-in-place. The study found affinity for technology was not a significant moderator for this cohort.